GG-07 SLE risk haplotypes are associated with development of serologic autoimmunity in healthy individuals. (31st August 2016) - Raj, Prithvi; Li, Quan-Zhen; Dozmorov, Igor; Olsen, Nancy J; Sivils, Kathy; Kelly, Jennifer; James, Judith A; Lauwerys, Bernard; Gregersen, Peter; Cerosaletti, Karen; Karp, David R; Wakeland, Edward K
Abstract : Background: Approximately 60 loci are associated with SLE in genotyping studies. These loci impact several pathways in the immune response. ANA are one of the earliest features of lupus, preceding the onset of clinical symptoms by many years. The genetic risk factors that underlie the development of serological autoimmunity are unknown. A genome-wide association study was undertaken to understand the genetics of ANA development Materials and methods: Serum and DNA were collected from 2, 635 healthy individuals with no personal history of autoimmunity. Antinuclear antibodies were detected using an ELISA to human nuclear extract (INOVA). Sera from 724 individuals (ANA-, ANA+, and SLE) were assayed by protein microarray quantifying IgM and IgG responses to 96 human autoantigens. A nested cohort of 1, 969 subjects consisting of all the ANA+ Caucasian individuals and age/gender matched ANA- controls were genotyped using the ImmunoChip SNP array. Results: In 2, 635 healthy individuals, 16.2% had moderate and 8.0% had high levels of IgG antinuclear antibodies. High titer ANA was almost exclusively seen in female subjects (OR (CI): = 1.6 (1.1–2.1), p = 0.003). Age was not associated with the presence or titer of ANA. On the autoantigen microarray, ANA+ healthy individuals had a high prevalence of antibodies to non-nuclear and cytoplasmic antigens, while subjects with SLE predictably produced antibodies to a variety of nuclear antigens. A quantitative genetic association test with ANA identified genomic loci associated with high ANA phenotype. HLA was second strongest signal (p = 6.2 × 10 -6 ). The frequencies of the SLE risk haplotypes at STAT4, TNFAIP3, BLK, BANK1, NCF2, and NMNAT2 were also significantly (p<0.05) increased in the ANA high positive group compared to ANA negative healthy subjects. On the other hand, SLE risk haplotypes in ITGAM, U BE2L3, IRF5-TNPO3 loci were only high in the SLE group, suggesting their main role in a transition to clinical disease. Conclusions: As has been seen in previous cohorts, a quarter of healthy individuals in this study made antinuclear antibodies, often at high titers. ANA testing, however, underestimates the repertoire of autoantibodies in these individuals. Healthy individuals who react in ANA testing produce antibodies against both non-nuclear and cytoplasmic antigens while SLE patients react to the classical RNA and DNA associated proteins. There is genetic risk for the development of ANA that includes many of the previously documented SLE risk haplotypes. However, other genetic associations are specific for SLE, suggesting distinct risk factors for ANA and for lupus.